Study and Implementation of Quality Improvement Techniques to Improve the Consistency in Cold Crushing Strength of Iron Ore Pellets - Sarda, Aditya; Nithesh, Naik; Krishna, Navneeth; Shrivastva, Tarun; Prabhu, Arun (Asian Journal of Engineering and Applied Technology, 2014)
Iron ore pellets plays vital role in the success of the steel industry across the globe. Maintaining consistent quality of pellets is very important to achieve good reducibility and productivity at both blast furnace and direct reduction processes. Physical parameters like cold crushing strength and shatter index of iron ore pellets are very critical for their handling and use. Cold crushing strength (CCS) of iron ore pellets varies widely from as low as 80 Kgf / pellets to as high as 350 Kgf /pellets depending upon the input material quality and the process variables. The most preferred range of CCS of iron ore pellets is 180-240 Kg f / pellets which were normally found in the proportion of 35-40% at the plant. The current investigation focuses on study and implementation of various quality improvement techniques to increase the proportion to the level of 60-70% and improve the cold crushing strength of iron ore pellets.